Economic crisis and democratic breakdown in the interwar years: a reassessment - Jørgen Møller; Alexander Schmotz; Svend-Erik Skaaning (Historical Social Research, 2015)
The `Great Recession' has rekindled discussions about the relationship between economic crisis and democratic breakdown, frequently based on analogies with interwar experiences. However, while the notion that economic crisis in general and the Great Depression in particular caused democratic breakdowns in the interwar years is widespread, most comparative studies of the period between the two world wars have found no independent effect of crisis on democratic breakdown. In this study, we argue that the latter findings are premised on inappropriate standards of assessments and the exclusion of relevant cases. Based on an event history analysis including 33 countries with democratic spells in the interwar years, we find a significant, non-trivial relationship between economic crisis and interwar democratic breakdown. Our results corroborate the notion that economic crisis substantially increases the risk of breakdown in fragile democracies. But we also show that it is not last year's economic performance that matters but rather longer-term developments.
Keywords: 300; economic crisis; democratic breakdown; event history analysis; interwar period